M-Current Suppression, Seizures and Lipid Metabolism: A Potential Link Between Neuronal Kv7 Channel Regulation and Dietary Therapies for Epilepsy - Hoshi, Naoto (Frontiers in Physiology, 2020)
Neuronal Kv7 channel generates a low voltage-activated potassium current known as the M-current. The M-current can be suppressed by various neurotransmitters that activate Gq-coupled receptors. Because the M-current stabilizes membrane potential at the resting membrane potential, its suppression transiently increase neuronal excitability. However, its physiological and pathological roles in vivo is not well understood to date. This review summarizes the molecular mechanism underlying M-current suppression, and why it remained elusive for many years. I also summarize how regulation of neuronal Kv7 channel contributes to anti-seizure action of valproic acid through inhibition of palmitoylation of a Kv7 channel binding protein, and discuss about a potential link with anti-seizure mechanisms of medium chain triglyceride ketogenic diet.